Communion with the Triune God : the Trinitarian Soteriology of T.F. Torrance. - Eugenio, Dick O. (James Clarke & Co, 2014)
For Thomas F. Torrance, the doctrine of the Trinity is always soteriological and soteriology is always Trinitarian. To isolate one from the other means to separate the Being of God from his Act, and vice versa. The distinct contribution of this book is that it consciously presents Torrance's soteriological Trinity and Trinitarian soteriology at the same time. In this book, soteriological Trinity refers to the fact that Torrance's doctrine of the Triune God is always a God with and for us. Dick Eugenio thus provides exhilarating new insights into what it means to be saved.